2012
DOI: 10.1167/iovs.11-8375
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Activation Maps for Longitudinal Studies of Visual Function by Functional Magnetic Resonance Imaging

Abstract: PURPOSE.To test the intra-and intersubject reproducibility of brain activation patterns that underlie visually guided saccades and word recognition in normally sighted subjects and patients with macular degeneration using functional magnetic resonance imaging (fMRI). METHODS.Ten normally sighted subjects and five patients with macular degeneration were asked to perform two visually guided saccade tasks and two word-recognition tasks during fMRI with behavioral monitoring. The fMRI measurements were repeated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(53 reference statements)
2
5
0
Order By: Relevance
“…It was also noted from Tables V and VI that ICC values computed using maximum and mean CNR of the first four sessions are usually greater than those calculated using all eight sessions. If we compare these ICC values to those from short-term studies (Ming et al, 2012, Kristo et al, 2014, similar observations can be made. This is reasonable considering the longterm and short-term factors described in the introduction.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…It was also noted from Tables V and VI that ICC values computed using maximum and mean CNR of the first four sessions are usually greater than those calculated using all eight sessions. If we compare these ICC values to those from short-term studies (Ming et al, 2012, Kristo et al, 2014, similar observations can be made. This is reasonable considering the longterm and short-term factors described in the introduction.…”
Section: Resultssupporting
confidence: 66%
“…A variety of studies have been conducted to examine fMRI reproducibility within a session (Tegeler et al, ), across multiple sessions for a single subject (McGonigle et al, ), and across multiple subjects and sessions (Rombouts et al, ; Specht et al, ; Wei et al, , Ming et al, , Kristo et al, ). Some studies were carried out during a relatively short period of time with two or more repeated sessions separated by a couple of hours, a few days, or up to 2 months (Rombouts et al, ; McGonigle et al, ; Specht et al, ; Ming et al, , Kristo et al, ). A small number of studies were performed to examine the long‐term fMRI reproducibility over 1 year, which is comparable to the time duration of clinical trials (Wei et al, ; Yoo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results are reported for resting-state fMRI studies (Blautzik et al, 2012;Meindl et al, 2010;Shehzad et al, 2009;Song et al, 2012). A recent eye movement study of the reliability of a saccadic task showed an interclass correlation coefficient of > 0.5 in 75% of the subjects studied (Ming et al, 2012). Further, studies report that reliability is improved when movement artifacts are small (Lund et al, 2005) and that 3-T scanners have better repeatability compared with 1.5-T scanners (Zou et al, 2005).…”
Section: Reliability Of Fmrisupporting
confidence: 79%
“…Anatomic imaging included nonvolumetric FLAIR imaging and volumetric MPRAGE sequences slices with slice gap of 0 mm) were acquired using clinical fMRI equipment (MRIv Technologies, Bannockburn, IL, USA) 15 and software to present a visually guided saccade for 30 seconds interleaved with 30 seconds of rest (repeated four times). 16 Diffusion and fMRI data sets then underwent spatial normalization to the MNI152 standard brain, 17 using a 12parameter affine coregistration algorithm (MINC tools; McConnell Brain Imaging Centre, http://www.bic.mni.mcgill.ca/ ServicesSoftware/MINC, available in the public domain), 18 and all datasets underwent rigorous quality assurance by an MR physicist (B.A.M.). A previously established and validated automatic diffusion tractography algorithm 10 was then used to identify and segment the OR.…”
Section: Methodsmentioning
confidence: 99%